Programming Fundamentals Using MATLAB - Weeks, Michael (Mercury Learning and Information, 2020)
This book covers the MATLAB syntax and the environment, suitable for someone with no programming background. The first four chapters present information on basic MATLAB programming including computing terminology, MATLAB specific syntax and control structures, operators, arrays, and matrices. The next cluster covers grouping data, working with files, making images, creating graphical user interfaces, experimenting with sound, and the debugging environment. The final three chapters contain case studies on using MATLAB and other tools and devices (e.g., Arduino, Linux, Git, Mex, etc.) important for basic programming knowledge. Companion files with code and 4-color figures are on the disc or available from the publisher.